Modeling a Fixed-Bed System with Coal Volatiles Post-Combustion for Ceramic Kiln Firing - Ardila Barragán , Marco Antonio; Triviño Restrepo, Maria del Pilar; Lozano Gómez, Luis Fernando; Ardila Otálora, Naren Natalia; Cruz Molina, Brigith Daniela; Jiménez López, Fabián Rolando; López-Díaz, Alfonso; Riaño Villamizar, Jaime Alberto (Ingeniería, 2025)
Context: It is estimated that, in Colombia, more than 1300 brick industries consume around 5800 Tcal/year, which are supplied by coal, biomass, wood, and gas combustion. The most commonly used kilns are down-draught, wherein coal combustion is produced on fixed-grate beds, emitting greenhouse gases and other pollutants. As a contribution to solving this problem, this work presents the model of a fixed-bed system with coal volatiles post-combustion. Method: Temperature, time, coal consumption, and combustion products were monitored in a down-draught kiln, in order to determine their mass, energy, and thermal efficiency balances. Coal characterization was performed under ASTM standards, ashes were determined via XRD, XRF, and TGA, and emissions were obtained using a gas analyzer. The thermodynamic model used to design the 3D reactor was based on coal-burning analysis. Results: The process lasted 3166 min, consuming 2150 kg of coal. The combustion gases exhibited a varying composition of CO2, CO, O2, and hydrocarbons. The temperature on the grate reached 900 °C, and we recorded 1000 °C in the dome and 600 °C at the chimney base. The temperature difference between the dome and the chimney base explains the heat transferred for ceramic baking. The calorific value of the char was 19.52% higher than that of the coal used. The composition of the ash showed silicon oxide, mullite, and goethite. The 3D model consists of a grate with preheater ducts for the secondary air post-combustion of the volatiles. Conclusions: The outcome of this research was the 3D model of a fixed-bed grate for coal combustion and volatiles post-combustion. With its implementation, we expect to improve air quality and reduce the effects of the process on human health, as well as its operating costs.